Experimental Study on Seismic Response of a Large-Span and Column-Free Subway Station in Composite Strata - Tingjin Liu; Siyuan Zheng; Xinwei Tang; Weixing Xu (Shock and Vibration)
In this paper, a shaking table test was conducted to investigate the seismic response of the large-span and column-free subway station in the upper-soft and lower-hard strata. The acceleration of the structure and the soil, the dynamic soil pressure, and the strain response of the subway station were obtained and analyzed. The results demonstrate the reasonable test design as the boundary effect was eliminated. The seismic response of the structure and soil became more severe as the acceleration amplitude of the input motion increased. It is indicated that possible shear damage of the soil and irreversible plastic deformation of the structure might have occurred as the test proceeded. The soft clay had a greater effect on the structure than that of the artificial rock. For the model structure, the tensile strain amplitude in the support region was larger than that in the midspan region. The support regions of the roof slab, lateral wall, and middle slab were the vulnerable components of the model structure during earthquakes.